AN EXPEDITIOUS AND GREEN APPROACH FOR THE SYNTHESIS OF 2-AMINO-4H-CHROMENES USING A CATALYST OF NATURAL ORIGIN - Bhosale, H. D.; Shisodia, S. U.; Ingle, R. D.; Kendrekar, P. S.; Shisodia, A. U.; Kótai, László; Pawar, R. P. (European Chemical Bulletin, 2018)
A highly efficient three-component one step system for the synthesis of 2-amino-4H-chromens is developed. Excellent yields were obtained simply by mixing malononitrile, aromatic aldehyde and α-napthol in lemon juice as a catalyst of natural origin and solvent, avoiding using hazardous organic solvents. The main advantages of this method are its green method character, short reaction time and simple workup procedures and the lack of using any metal containing catalysts.
Published Article
Keywords: Green synthesis; benzaldehyde; malononitrile; catalyst of natural origin; ultrasound; 2-amino-4H-chromenes